Black and white cinema : a short history - Dixon, Wheeler W., 1950- (Rutgers University Press, 2015)
Black and White Cinema is the first study to consider black-and-white film as an art form in its own right, providing a comprehensive and global overview of the era when it flourished, from the 1900s to the 1960s. Including over forty stills that give us a unique glimpse behind the scenes, Wheeler Winston Dixon introduces us to the masters of this art, including directors, set designers, and award-winning cinematographers like James Wong Howe, Freddie Francis, and Sven Nykvist.